Survey of Lung Function and Respiratory Symptoms Among Online Motorcycle Taxi Drivers in Bekasi City - Damayanti, Triya; Pradipta, Jaka; Rahmawati, Ismulat; Harlivasari, Annisa Dian; Prasetyo, Erry; Anggara, Bobby (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: Online motorcycle taxi drivers have been heavily exposed to high concentration of hazardous air pollutants. This study aimed to describe the lung function and respiratory symptoms among online motorcycle taxi drivers and risk factors which influence them. Methods: The study design was survey research design with sample number of 99 online motorcycle taxi drivers in Bekasi City. Lung function examination was done using spirometer (Spirolab) and the predicted value of lung function was using Pneumobile Project Indonesia. Risk factors and respiratory symptoms were collected using questionnaire. Results: There were 10.1% of subjects with restrictive lung function and 5.1% with obstructive impairment. There were significant association between age of the drivers with restrictive disorders (P=0.006) and the mean difference of %FEV1 (P=0.039). There was a significant relationship between sex (P=0.001) and age (P=0.001) with the mean percent of forced vital capacity (%FVC). The respiratory symptoms collected were cough (17.2%) and shortness of breath (6.1%). There were no significant relationship between respiratory symptoms and lung function. Conclusions: Online motorcycle taxi drivers had respiratory symptoms and lung function impairment, however the causal relationship with the workplace environment is still unclear. Moreover, education about the importance of using personal protective equipment is needed to protect respiratory systems from harmful substances. (J Respir Indo 2019; 39(1))